Large Potential for CH 4 Mitigation and Yield Improvement in China's Paddies Through Locally Optimized N Management - Haoyu Qian; Zhengqi Yuan; Xiangcheng Zhu; Yuanfa Huang; Min Li; Jiarui Li; Yuxin Ren; Jinfei Feng; Shan Huang; Wenjun Dong; Feng Jin; Jiping Gao; et al. (Global Change Biology, 2026)
Nitrogen (N) management is critical for ensuring food security and mitigating greenhouse gas (GHG) emissions. In rice paddies, the effectiveness of N management in maximizing yields and minimizing N losses is highly dependent on local environmental conditions and thus varies widely across regions. However, the influence of optimized, site‐specific N management on methane (CH 4 ) emissions remains poorly quantified and is not reflected in current IPCC Tier 1 methodologies. Here, we synthesize data from multiregional field experiments and conduct a meta‐analysis to show that locally optimized N management practices—such as delayed fertilizer application, reduced N input, and deep placement—reduce CH 4 emissions from rice paddies by 16%–21%. The experiments further show that these practices suppress CH 4 emissions by lowering soil N availability and organic matter decomposition, thereby limiting substrates for methanogenesis. Combining survey data from 155 counties with machine learning models, we estimate that implementing optimized N strategies across China's rice‐growing regions could reduce CH 4 emissions by 16% while simultaneously increasing rice yields by 7%. These findings underscore the dual benefits of locally optimized N management for agricultural productivity and climate change mitigation, and provide a foundation for improving CH 4 emission estimates under diverse management regimes.